2015
DOI: 10.1167/iovs.14-16247
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of L-Carnitine Against Oxidative Injury by Hyperosmolarity in Human Corneal Epithelial Cells

Abstract: Our findings demonstrate for the first time that L-carnitine protects HCECs from oxidative stress by lessening the declines in antioxidant enzymes and suppressing ROS production. Such suppression reduces membrane lipid oxidative damage markers and mitochondrial DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…The reason may be that the pro-inflammatory cytokines IL-1β and TNF-α just caused transient inhibition of stemness and the cell cycle, while hyperosmotic stress not only caused the suppression of stemness but also induced more severe cell apoptosis, necrosis, and a cell cycle arrested at the G2/M phase in CESCs, all of which are physiologic changes that cannot be recovered in a short time after treatment. In addition, several studies have demonstrated that hyperosmotic stress can raise the production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, TGF-β1, and IL-23) and chemokines (IL-8, CCL2, and CCL20) at mRNA and protein levels in human corneal epithelial cells [34,65]. Our findings also confirmed that hyperosmosis treatment promoted the expression of TNF-α, IL-1β, MCP-1, and IL-8 both in cultured corneal epithelial stem/progenitor cells and corneal injury mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that the pro-inflammatory cytokines IL-1β and TNF-α just caused transient inhibition of stemness and the cell cycle, while hyperosmotic stress not only caused the suppression of stemness but also induced more severe cell apoptosis, necrosis, and a cell cycle arrested at the G2/M phase in CESCs, all of which are physiologic changes that cannot be recovered in a short time after treatment. In addition, several studies have demonstrated that hyperosmotic stress can raise the production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, TGF-β1, and IL-23) and chemokines (IL-8, CCL2, and CCL20) at mRNA and protein levels in human corneal epithelial cells [34,65]. Our findings also confirmed that hyperosmosis treatment promoted the expression of TNF-α, IL-1β, MCP-1, and IL-8 both in cultured corneal epithelial stem/progenitor cells and corneal injury mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…L‐carnitine (Hua et al. ) and pterostilbene (Li et al. ), a blueberry component, were found to be able to reduce oxidative stress induced by hyperosmolarity in cultured cells.…”
Section: Preclinical Intervention Studiesmentioning
confidence: 99%
“…Both molecules were able to reduce the levels of oxidative damage biomarkers and inflammatory mediators, with associated reduction in the levels of antioxidant enzymes (Hua et al. ; Li et al. ).…”
Section: Preclinical Intervention Studiesmentioning
confidence: 99%
“…Osmoprotectants such as L-carnitine, erithritol, or betaine have been shown to significantly reduce HO-induced proinflammatory responses, 15 to promote the survival of corneal epithelial cells, and protect the integrity of the epithelium. [16][17][18] We therefore tested the effects of these molecules on wound healing under HO conditions ( Figure 5). Although L-carnitine and erithritol proved ineffective (Figures 5a and c), betaine showed a concentration-dependent improvement in HO wound healing (Figure 5b).…”
Section: Effects Of Osmoprotectants On Ho Cytotoxicity and Rgtasmentioning
confidence: 99%